2019
DOI: 10.1007/s00253-019-09708-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and prioritizing biosynthetic gene clusters for bioactive compounds in bacteria and fungi

Abstract: Secondary metabolites (SM) produced by fungi and bacteria have long been of exceptional interest owing to their unique biomedical ramifications. The traditional discovery of new natural products that was mainly driven by bioactivity screening has now experienced a fresh new approach in the form of genome mining. Several bioinformatics tools have been continuously developed to detect potential biosynthetic gene clusters (BGCs) that are responsible for the production of SM. Although the principles underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 105 publications
2
70
0
Order By: Relevance
“…Analysis of association of P450s with BGCs revealed that specific P450 orthologues are involved in the production of the same secondary metabolite (Table 4), indicating horizontal gene transfer of these BGCs among Bacillus species, a well-known phenomenon of gene-cluster transfer between bacterial species 33,64,65 . Prominent observations include CYP107K P450s' involvement in biosynthesis of bacillaene, CYP113L1 P450s' involvement in the biosynthesis of difficidin and CYP107H4 P450s' involvement in the biosynthesis of fengycin (Table 4).…”
Section: Most Firmicutes Species P450s Are Orphans Of Unknown Functiomentioning
confidence: 99%
“…Analysis of association of P450s with BGCs revealed that specific P450 orthologues are involved in the production of the same secondary metabolite (Table 4), indicating horizontal gene transfer of these BGCs among Bacillus species, a well-known phenomenon of gene-cluster transfer between bacterial species 33,64,65 . Prominent observations include CYP107K P450s' involvement in biosynthesis of bacillaene, CYP113L1 P450s' involvement in the biosynthesis of difficidin and CYP107H4 P450s' involvement in the biosynthesis of fengycin (Table 4).…”
Section: Most Firmicutes Species P450s Are Orphans Of Unknown Functiomentioning
confidence: 99%
“…[17] Direct digital extraction of chemical shifts from the raw data [18] will push the protocol closer to native computational interrogation. This in turn will expedite the growth of the database,which we anticipate will eventually be able to assign the structural features of each carbon and proton within ag iven molecule.W hile structural assignment is ak ey facet of the drug discovery process,t he ability to search through molecular data one atom at at ime offers an ew perspective that can enable this system to operate through aconventional online portal, one that ideally will be united with biosynthetic genome mining tools [19] such as antiSMASH, [20] as well as proteomic [21] and transcriptomic [22] data. Ultimately,i tw ill be interesting to understand the correlation between structural novelty and its role in inducing novel biological activity,p erhaps done best one atom at atime.…”
mentioning
confidence: 99%
“…It has been reported that most BGCs remain silent and cannot be fully expressed under standard laboratory conditions. These silent BGCs are potentially significant in the discovery of novel SMs [10][11][12]43].…”
Section: Genomic For Screening and Enhancement Of Sms 21 Gene Editinmentioning
confidence: 99%